ANALISIS STRATEGI PEMBERDAYAAN EKONOMI MASYARAKAT KAMPUNG SUSTAINABLE DEVELOPMENT GOALS (SDGS) DALAM PENINGKATKAN KESEJAHTERAAN - Siti Nur Azizatul Luthfyah; Nurul Widyawati Islami Rahayu; Abdul Rokhim (Faculty of Islamic Economics and Business, 2022)
Community empowerment is a series of activities to strengthen funds or maximize the empowerment of a person or community. In the sense of increasing the ability of the weak and vulnerable groups, including groups of people who experience poverty problems. In practice, community empowerment also supports the United Nations (UN) program which has undergone a change from the Millennium Development Goals (MDG's) in 1990-2015 to become sustainable development goals or commonly called TPB or Sustainable Development Goals (SDGs) which is on the 2030 agenda. under development. Many institutions are trying to improve development, both from community and government institutions. The PPPKSI (Indonesian SDGs Village Development Center) institution is no exception, which responds to sustainable development efforts by establishing SDGs Villages. This SDGs village is an area unit at the hamlet level that has certain criteria where there is an integrated Sustainable Development Goals program that is carried out comprehensively and systematically. Data collection techniques used are observation, interviews, and documentation. Then the process of analyzing the data using data analysis proposed by Miles and Huberman which consists of several activities including: data collection, data reduction, data presentation, and data verification. The results of the study explain that the analysis of the economic empowerment strategy of the SDGs village community is: a) the formulation is carried out with preparation, assessment and program planning. b) implementation is carried out by implementing the program plan. c) evaluation in the form of measurement and separation of partners. While the impact is increased knowledge and income to meet needs. The supporting factors are the availability of raw materials, human resources, and a fairly easy process, while the obstacles are the lack of capital and unstable marketing.